Ecotoxicological and microbiological assessment of sewage sludge associated with sugarcane bagasse - Sommaggio, Lais Roberta Deroldo [UNESP]; Mazzeo, Dânia Elisa Christofoletti [UNESP]; Sant’ Anna, Débora de Andrade e Silva; Levy, Carlos Emílio; Marin-Morales, Maria Aparecida [UNESP] (Elsevier, 2018)
Sewage sludge (SS) obtained after sewage treatment process may contain several toxic substances. Bioremediation can decrease the toxicity of the sludge, mainly when it is associated with stimulant agents, such as sugarcane bagasse (B). Samples of pure SS (SSP); SS+B; SS+Soil; and SS+B+Soil were bioremediated for 1, 3, and 6 months (T1, T2, and T3, respectively). After each period, the cytotoxic, genotoxic, and mutagenic potentials of the solid samples and their respective aqueous extracts (aqueous eluate and percolate water) were evaluated by the Allium cepa test. A microbiological analysis of the samples was also performed after each period tested. All solid samples of SS+B (in T1, T2, and T3) and the solid sample of SSP (treatment T3) showed a significant decrease of cell division (cytotoxic effects). The aqueous eluate extracts of SS+B (T1 and T3) and SSP (T2 and T3) induced cytotoxic effect. The solid sample of SS+B (T2 and T3) and aqueous extracts of SSP (T1) were genotoxic, indicating a harmful effect of SS on A. cepa, even after 6 months of bioremediation. There was an alternation in the microbial community both in diversity and in abundance, with the predominance of nonfermenting gram-negative bacilli. The tested bioremediation periods were not sufficient for the complete detoxification of SS, and the use of B did not seem to contribute to the degradation of the pollutants to inert compounds. These data emphasize that a specific relationship should exist between the sludge characteristic and the biostimulating agent used to promote a more efficient bioremediation. These results suggest the necessity to study longer periods of biodegradation and the use of other decomposing agents for greater safety and sustainability for the agricultural use of this residue.
Keywords: Allium cepa; Chromosomal aberrations; Microbiological characterization; Micronucleus; Residue management